Antiviral activity of the adenosine analogue BCX4430 against West Nile virus and tick-borne flaviviruses - Eyer, Luděk; Zouharová, Darina; Širmarová, Jana; Fojtíková, Martina; Štefánik, Michal; Haviernik, Jan; Nencka, Radim; de Clercq, Erik; Růžek, Daniel (Antiviral research, 2017)
There are currently no approved antiviral therapies against medically important human flaviviruses. The imino-C-nucleoside BCX4430 shows broad-spectrum antiviral activity against a wide range of RNA viruses. Here, we demonstrate that BCX4430 inhibits tick-borne species of the genus Flavivirus; however, the antiviral effect varies against individual species. Micro-molar BCX4430 levels inhibited tick-borne encephalitis virus (TBEV); while, approximately 3-8-fold higher concentrations were needed to inhibit louping ill virus and Kyasanur Forest disease virus. Moreover, the compound strongly inhibited in vitro replication of West Nile virus, a typical mosquito-transmitted flavivirus. Two chemical forms of the compound, i.e. BCX4430 and BCX4430 hydrochloride, were compared and both exerted similar inhibitory profiles in our in vitro antiviral assay systems and no or negligible cytotoxicity in porcine kidney stable and Vero cells. The obtained data indicate that, in addition to mosquito-borne flaviviruses, the compound has strong antiviral activity against members of the TBEV serocomplex.
Keywords: prasata; Tick-Borne Diseases; adenosin; Swine; viabilita buněk; Cell Line; Antiviral activity; klíšťata; Cercopithecus aethiops; replikace viru; West Nile virus; Adenine; Purine Nucleosides; Pyrrolidines; Nucleoside inhibitor; antivirové látky; adenin; Ticks; vztah mezi dávkou a účinkem léčiva; purinové nukleosidy; Cell Survival; Encephalitis Viruses, Tick-Borne; pyrrolidiny; Chlorocebus aethiops; BCX4430; Encephalitis, Tick-Borne; nemoci přenášené klíšťaty; Animals; Antiviral Agents; Cytotoxicity; Virus Replication; Flavivirus; zvířata; klíšťová encefalitida; Culicidae; virus západního Nilu; buněčné linie; Vero Cells; viry klíšťové encefalitidy; Adenosine analogue; Adenosine; Dose-Response Relationship, Drug; Vero buňky